Palpolas: The Symbolic Betting Arena of The Taba People - Sahar, Santri; Anggariani, Dewi (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
Palpolas in Taba language means payment. The payment in question is the surrender of a sum of money made by members of the local community on the tenth day of the death ceremony because it costs up to hundreds of millions of rupiah. The results of observations and interviews at the research location using the Bourdieu Practical Theory guide show that Palpolas is basically a reciprocal in overcoming the costs of the death ritual, but the ritual owner tries to collect a source of capital, by displaying symbols of kinship clans in a sacred room when bathing the corpse. , burial and Tapin (ritual center), so that it appears a knot that the local community is one family so they voluntarily pay for the ritual. In practice, there was a gamble between the family of the ritual owner and the general public at the time of Palpolas. The owner of the ritual tries to show a symbol of social prestige by minimizing the public debt that must be paid off, while the public wants to show a symbol of dominance by depositing Palpolas money more than once